Respuesta :

Answer:

Step-by-step explanation:

7) [tex]n-\frac{8}{9}=\frac{4}{9}[/tex]

  [tex]n-\frac{8}{9}+\frac{8}{9} =\frac{4}{9}+\frac{8}{9}[/tex]

  n = [tex]\frac{4+8}{9}[/tex]

  n = [tex]\frac{12}{9}[/tex]

 n = [tex]\frac{4}{3}[/tex]

8). [tex]\frac{3}{2}+x=-\frac{7}{2}[/tex]

   [tex]\frac{3}{2}+x-\frac{3}{2} =-\frac{7}{2}-\frac{3}{2}[/tex]

   x = [tex]-\frac{7+3}{2}[/tex]

   x = -5

9). [tex]\frac{6}{5}= \frac{d}{\frac{5}{4}}[/tex]

   d = [tex]\frac{6}{5}\times \frac{5}{4}[/tex]

   d = [tex]\frac{6}{4}[/tex]

  d = [tex]\frac{3}{2}[/tex]

10). [tex]-\frac{1}{8}V=\frac{5}{2}[/tex]

    [tex]-\frac{1}{8}V\times (-8)=\frac{5}{2}\times (-8)[/tex]

    V = -20